Plant Parts and their Functions Visualized through E-Storybook Learning Media: Is It Feasible? - Ni Wayan Adnyanawati; Ida Bagus Gede Surya Abadi (Universitas Pendidikan Ganesha, 2021)
Online learning due to the Covid-19 pandemic raises problems for students due to the lack of learning media that supports the learning process. This research aims to know the design of the media and know the feasibility of E-Storybook learning media on plant parts material and its function in the science content of Grade IV Elementary School. The ADDIE development model is the model used in this study. This research stage consists of analysis stage (Analyze), design stage (Design), development stage (Development), implementation stage (Implementation), and evaluation stage(Evaluation). The subject of this study is the learning medium E-Storybook. Data collection techniques using questionnaire methods. The data collected in quantitative descriptive analysis and qualitative descriptive data analysis. Product validation is done by 3 experts, namely learning content experts, learning design experts and learning media experts. The results showed that the average validity score of content experts is 92% with excellent qualifications, the average validity score of learning design experts is 93% with excellent qualifications, the average score of learning media experts is 95% with excellent qualifications and the average result of 3 respondents is 92.7% with excellent qualifications. Thus the learning media of E-Storybook has been declared eligible for use in online learning.